Outcomes and predictors of harmful relapse following liver transplantation for alcoholic liver disease in an Australian population. Issue 6 (June 2017) - Wigg, Alan J.; Mangira, Dileep; Chen, John W.; Woodman, Richard W.
Abstract : Background: Limited studies of patient survival and alcoholic relapse following transplantation for alcoholic liver disease have been described in Australian populations. Aim: To describe these outcomes in an Australian population, to determine the association between harmful alcoholic relapse and patient survival, and to examine pre‐transplant variables associated with harmful relapse. Methods: Single centre, retrospective review of consecutive patients transplanted at the South Australian Liver Transplant Unit. Relapse was identified by an independent investigator using case note review and confidential patient questionnaire. Results: A total of 87 patients (median age 52 years, 84% male, median Model for End‐Stage Liver Disease (MELD) score 18) was included in the study with a median follow‐up time of 50 months. The 1‐, 3‐ and 5‐year survival of patients was 93.1, 87.4 and 82.0% respectively. Two deaths were directly attributable to graft failure due to alcohol. Fourteen (16%) patients fulfilled criteria for harmful relapse and 18 (21%) patients experienced any form of relapse to alcohol. Harmful relapse was associated with increased mortality (hazard ratio (HR) 3.2, 95% confidence interval (CI) 1.1–9.7, P  = 0.041). Only two factors were independently associated with harmful relapse on multivariate analysis; prior alcohol rehabilitation (HR 8.4, 95% CI 2.5–28.4, P  = 0.001) and single versus married status (HR 0.09, 95% CI 0.02–1.2, P  = 0.019). Conclusion: Good patient survival outcomes were seen for this South Australian population. Harmful alcohol relapse occurs in a minority of patients and rarely results in direct graft loss. Modifiable pre‐transplant factors that predict harmful relapse were not identified.